Analytical Study on Integration of Islamic Science in Indonesia Based on Ontology, Epistemology, and Axiology - Lubis, Faizal; Salminawati, Salminawati; Usiono, Usiono; Rusdi, Muhammad (Southeast Asian Journal of Islamic Education, 2024)
The concept of knowledge or truth can vary among various scientific traditions. Integrating various epistemological approaches, such as Islamic and modern scientific epistemologies, becomes complex. There are differences in understanding the integration of Islamic science and traditions among Islamic scholars and other scientists. Understanding these differences and trying to integrate multiple perspectives becomes a challenge. This research aimed to analyze the integration of Islamic science in Indonesia based on ontology, epistemology, and axiology points of view. This research was conducted using library research. The objects in this research were searched using various library information such as books, scientific journals, magazines, newspapers and documents. The research results show that an analytical study on the integration of Islamic science in Indonesia based on ontology, epistemology and axiology at the Indonesian Islamic University can cover several essential aspects. Islamic Scientific Ontology includes an understanding of the nature of science in the Islamic context. This includes questions about the sources of knowledge in Islam, whether the Islamic scientific ontology at the Islamic University of Indonesia recognizes the Qur’an and hadith as the primary sources or whether there are additions from other philosophical or scientific traditions. Islamic Scientific Epistemology focuses on the methodology and approaches used in building and developing Islamic scientific knowledge. Islamic Scientific Axiology investigates the values ​​or principles underlying the use of Islamic scientific knowledge and their ethical implications. This involves considering how Islamic scientific knowledge is used and applied in the Indonesian social and cultural context and its impact on society.